Weed Control in Leafy Greens (Lettuce, Endive, Escarole, and Spinach) - William M. Stall (EDIS)
Revised! HS203, a 4-page fact sheet by William M. Stall, provides updated recommendations for weed control in leafy greens. Published by the UF Department of Horticultural Sciences, March 2010.